Legal Research dan Epistemologi Fiqh Al-Syathibi Perspektif Rosedur Ilmiah - Muhaki (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2023)
In the contemporary century, the theory of Islamic law, which is much highlighted is maqashid al-syari'ah and al-mashlahah, but for classic scholars maqashid is only a principle of syari'ah. In contrast to the concept of al-Syathibi, who constructs it as an epistemology of fiqh by placing scientific legal research procedures. The problem is, First, how is the epistemology of fiqh in al-Syathibi's construction? Second, how is the scientific procedure of legal research in al-Syathibi's fiqh epistemology? Third, how is the scientific product of al-Syathibi's legal research activities? Based on the descriptive method it was found: First, the epistemological construction of al-Syathibi's fiqh is built on empirical premises, rational but not subject to causality, and all processes are carried out based on scientific procedures. Second, the scientific procedure used is the inductive method to arrive at generalizations, and for application to legal cases that occur it is based on the deductive method. Third, through clinical legal research, al-Syathibi shows the findings of maqashid al-syari'ah as systematic knowledge that is universal. The conclusion is that fiqh provisions must be deduced from the legal research process by placing tahqiq al-manat (relevant fiqh facts), and generalizing them using inductive methods. Meanwhile, the benchmark for truth is no longer the strength of the text's argument, but its philosophical values and universal values, so that if there is a fiqh problem, it can be deduced from it.